2017
DOI: 10.1002/jcp.26201
|View full text |Cite
|
Sign up to set email alerts
|

Loss of RUNX1 is associated with aggressive lung adenocarcinomas

Abstract: The mammalian runt-related factor 1 (RUNX1) is a master transcription factor that regulates lineage specification of hematopoietic stem cells. RUNX1 translocations result in the development of myeloid leukemias. Recently, RUNX1 has been implicated as a tumor suppressor in other cancers. We postulated RUNX1 expression may be associated with lung adenocarcinoma etiology and/or progression. We evaluated the association of RUNX1 mRNA expression with overall survival data from The Cancer Genome Atlas (TCGA), a publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…[9][10][11][12][13] Runt domain transcription factor (RUNX) family is mainly composed of RUNX1, RUNX2, RUNX, 14 and the functions of these three factors are slightly different. [16][17][18] LncRNA RUNX1-IT1 is the intronic transcript 1 of the RUNX1, which is also known as chromosome 21 open reading frame 96 (C21orF96). 15 Besides, RUNX1 has also been reported as a tumour suppressor in many cancers, such as gastric cancer, lung adenocarcinomas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13] Runt domain transcription factor (RUNX) family is mainly composed of RUNX1, RUNX2, RUNX, 14 and the functions of these three factors are slightly different. [16][17][18] LncRNA RUNX1-IT1 is the intronic transcript 1 of the RUNX1, which is also known as chromosome 21 open reading frame 96 (C21orF96). 15 Besides, RUNX1 has also been reported as a tumour suppressor in many cancers, such as gastric cancer, lung adenocarcinomas.…”
mentioning
confidence: 99%
“…15 Besides, RUNX1 has also been reported as a tumour suppressor in many cancers, such as gastric cancer, lung adenocarcinomas. [16][17][18] LncRNA RUNX1-IT1 is the intronic transcript 1 of the RUNX1, which is also known as chromosome 21 open reading frame 96 (C21orF96).…”
mentioning
confidence: 99%
“…Two key noncoding RNAs (RUNX1-IT1 and ANP32A-IT1) were identi ed as effective diagnostic genes in the present study. LncRNA RUNX1-IT1, and ANP32A-IT1 are the intronic transcript 1 from their respective genes [64,65]. RUNX1 IT1 plays a tumour suppressive role and plays aprotective role in colorectal cancer by regulating cell proliferation, migration, and apoptosis [65].…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor Runx1 has been identified as being involved in Gal-3 expression [30]. However, a previous study reported that the knockdown of RUNX1 increased lung cancer cell growth and motility, and lung cancer patients with low RUNX1 exhibit a poor prognosis [28]. Intriguingly, there is no report of FOXD1 being associated with Gal-3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular Gal-3 acts as a mediator that regulates metastatic cancer processes by recognizing N-acetyllactosamine (β-galactoside)-conjugated proteins, including EGFR, integrins, TGF-β receptors, etc. [25,27,28]. For instance, the interaction of integrin β3 and Gal-3 contributes to EGFR tyrosine kinase inhibitor resistance, which facilitates lung cancer cell stemness properties and renders them more resistant to chemotherapeutic agents [29].…”
Section: Introductionmentioning
confidence: 99%